Improving charge separation across a hybrid oxide/polymer interface by Cs doping of the metal oxide - Sevinchan, Yunus; Hopkinson, Paul E.; Herz, Julia; Motzkus, Marcus; Vaynzof, Yana (Advanced materials interfaces, 2016)
The process of photoinduced charge carrier separation in hybrid optoelectronics remains only partially understood, with the mechanism behind creation and dissociation of bound charge pairs (BCPs) being open questions. To investigate these processes, the model hybrid ZnO/poly(3-hexylthiophene) system is employed and it is shown that Cs doping of ZnO results in a decrease in the density of gap states at the metal oxide surface and, in turn, a reduction in the yield of BCPs. This provides direct experimental evidence for a previously proposed model of BCP creation by electron trapping at the metal oxide surface states. Furthermore, Cs doping is found to substantially increase the open circuit voltage in these devices without the negative effects on the short circuit current which were observed in studies with other dopants. This offers new possibilities for hybrid photovoltaic devices with increased power conversion efficiencies and provides valuable insights on the charge separation processes in hybrid organic-inorganic photovoltaics.
Gesehen am 05.05.2020